Fraksionasi Metil Ester Asam Lemak (Biodiesel) Menggunakan Pelarut Urea - Komang, Hendri; Helwani, Zuchra; Zahrina, Ida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Biodiesel / Fatty Acid Methyl Ester (FAME) is a renewable fuel. However, biodiesel circulating in the market has the disadvantage of low oxidation stability. To improve the quality of biodiesel, biodiesel fractions are separated. The saturated and monounsaturated fractions have ideal properties as biodiesel and the polyunsaturated fraction has a very low oxidation stability which is undesirable in biodiesel. Urea complexation is one of the ways separating biodiesel fractions, and methanol is one of the commonly used solvents. As a parameter of the success of separation iod numbers are tested. The optimum condition for biodiesel separation is determined by the effect of the FAME: urea ratio and the FAME: methanol ratio. At optimal separation, the biodiesel iodine was 58.13, ie at the FAME:urea ratio of 1:3 and the FAME:methanol ratio of 1:3. The separated polyunsaturated FAME fraction can be used in the oleochemical industry and other processes that require a high degree of unsaturation. Keywords: biodiesel/FAME, oxidation stability, urea complexation, saturated and unsaturated